PENGARUH TUNJANGAN KINERJA DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN BADUNG - Ni Kadek Dwi Ayu Damayanti; Ida Bagus Made Widiadnya; Sapta Rini Widyawati (VALUES, 2022)
Employee performance is one of the important aspects that must be considered by the organization, because employee performance requires the organization to achieve its goals. Constraints contained in an agency usually decrease the level of performance of the employee this can be caused by the factor of providing performance allowances for employees and promotions held in each agency. The purpose of this study was to determine the effect of performance allowances and promotions simultaneously on employee performance in Civil Servants at the Communication and Information Office of Badung Regency. This research was conducted at the Department of Communication and Information, Badung Regency. The population in this study is the Civil Servants of the Communication and Information Office of Badung Regency as many as 45 people. The selected sample is 45 respondents to Civil Servants at the Communications and Information Office of Badung Regency. The analytical technique used in this research is Multiple Linear Regression Analysis. The results of the study show (1) the performance allowance has a positive and significant effect on employee performance at the Communication and Information Office of Badung Regency, (2) Job promotion has a positive and significant effect on employee performance at the Communication and Information Office of Badung Regency.